Repair of residual aortic dissections with frozen elephant trunk technique - Akbulut, Mustafa (Turk Gogus Kalp Damar Cerrahisi Derg, 2020)
BACKGROUND: In this study, we present our mid-term results of reoperation with the frozen elephant trunk procedure due to patent false lumen-related complications in patients previously undergoing supracoronary aortic repair for acute type A aortic dissection. METHODS: Between January 2013 and September 2018, a total of 23 patients (17 males, 6 females; mean age 51.5±9.7 years; range, 30 to 67 years) who underwent ascending aortic replacement due to type A aortic dissection and, later, frozen elephant trunk procedure for residual distal dissection were included. For diagnostic purposes and follow-up, computed tomography angiography was performed in all patients, and both re-entry and aortic diameters were evaluated. Echocardiography was used to evaluate cardiac function and valve pathologies. RESULTS: The Ishimaru zone 0 (n=11, 47.8%), Ishimaru zone 1 (n=1, 4.3%), Ishimaru zone 2 (n=4, 17.4%), and Ishimaru zone 3 (n=7, 30.4%) were used for frozen elephant trunk stent graft fixation. The mean duration of cardiopulmonary bypass and antegrade selective cerebral perfusion was 223.9±71.2 min and 88.9±60.3 min, respectively. In-hospital mortality was 13%, while there was one (4.3%) aortic-related death and four (17.4%) re-interventions during follow-up. CONCLUSION: Early repair should be considered in the presence of persistent dissections due to alarmingly high mortality rates of reoperations. Reoperation with the frozen elephant trunk procedure has acceptable results and the decision of the procedure to be performed should be based on preoperative risk factors of the patient.